Gamification for Better Travel Planning - Nanda Feronika, Taufiq Maulana Asmoyo, Emil R. Kaburuan, Gunawan Wang (International Journal of Advanced Science and Technology, 2020)
The number of tourists is growing. Along with that, the efforts of government to make a better experience for tourism are continuously increasing including the policy, infrastructure, and so on. For that, we want to develop an application that can integrate all information and make estimated costs for travel. This application will apply the gamification method. Gamification is a method of using elements and features in a game with the aim of giving a pleasant impression and helping the learning process.